# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime }+y \sin \left (x \right ) = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }+y = \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{2}+1}\, y^{\prime }+y = 2 x
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{2}+1}\, y^{\prime }-y = 2 \sqrt {x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}\sqrt {\left (x +a \right ) \left (x +b \right )}\, \left (2 y^{\prime }-3\right )+y = 0
\] |
✓ |
✓ |
|
\[
{}\sqrt {\left (x +a \right ) \left (x +b \right )}\, y^{\prime }+y = \sqrt {x +a}-\sqrt {x +b}
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime } y^{2} = 2 x -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 6 x y^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{y} \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \sec \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = 3 \cos \left (y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {4 x y}{x^{2}+1}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 y}{x^{2}-1}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = 0
\] |
✓ |
✓ |
|
\[
{}\cot \left (x \right ) y^{\prime } = y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = x \,{\mathrm e}^{-2 y}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-2 x y = 2 x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x y+y
\] |
✓ |
✓ |
|
\[
{}\left (x^{3}+1\right ) y^{\prime } = 3 x^{2} \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x \cos \left (y\right ) y^{\prime } = 1+\sin \left (y\right )
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = 2 y \left (y-1\right )
\] |
✓ |
✓ |
|
\[
{}2 x y^{\prime } = 1-y^{2}
\] |
✓ |
✓ |
|
\[
{}\left (1-x \right ) y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-1\right ) y^{\prime } = \left (x^{2}+1\right ) y
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x} \left (1+y^{2}\right )
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{y} y^{\prime }+2 x = 2 x \,{\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}y \,{\mathrm e}^{2 x} y^{\prime }+2 x = 0
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = \sqrt {y^{2}-9}
\] |
✓ |
✓ |
|
\[
{}\left (x +y-1\right ) y^{\prime } = x -y+1
\] |
✓ |
✓ |
|
\[
{}x y y^{\prime } = 2 x^{2}-y^{2}
\] |
✓ |
✓ |
|
\[
{}x^{2}-y^{2}+x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }-2 x y-2 y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime } = 3 \left (x^{2}+y^{2}\right ) \arctan \left (\frac {y}{x}\right )+x y
\] |
✓ |
✓ |
|
\[
{}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )+x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+2 \,{\mathrm e}^{-\frac {y}{x}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (x +y\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \sin \left (x -y+1\right )^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+4}{x -y-6}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x +y+4}{x +y-6}
\] |
✓ |
✓ |
|
\[
{}\left (x +\frac {2}{y}\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \tan \left (y\right )+1+\cos \left (x \right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✗ |
|
\[
{}y-x^{3}+\left (y^{3}+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{2}-4 x +5 = \left (4-2 y+4 x y\right ) y^{\prime }
\] |
✗ |
✗ |
|
\[
{}y+y \cos \left (x y\right )+\left (x +x \cos \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right ) \cos \left (y\right )^{2}+2 \sin \left (x \right ) \sin \left (y\right ) \cos \left (y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (\sin \left (x \right ) \sin \left (y\right )-x \,{\mathrm e}^{y}\right ) y^{\prime } = {\mathrm e}^{y}+\cos \left (x \right ) \cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}-\frac {\sin \left (\frac {x}{y}\right )}{y}+\frac {x \sin \left (\frac {x}{y}\right ) y^{\prime }}{y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}1+y+\left (1-x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 x y^{3}+y \cos \left (x \right )+\left (3 x^{2} y^{2}+\sin \left (x \right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}1 = \frac {y}{1-x^{2} y^{2}}+\frac {x y^{\prime }}{1-x^{2} y^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (3 x^{2}-y^{2}\right ) y^{\prime }-2 x y = 0
\] |
✓ |
✓ |
|
\[
{}x y-1+\left (x^{2}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +3 y^{4} x^{3}\right ) y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -1-y^{2}\right ) y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y-\left (x +x y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = x^{5}+y^{2} x^{3}+y
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime } = y-x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = y+x^{2}+9 y^{2}
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-3 y = x^{4}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = \frac {1}{1+{\mathrm e}^{2 x}}
\] |
✓ |
✓ |
|
\[
{}2 x y+\left (x^{2}+1\right ) y^{\prime } = \cot \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y = 2 x \,{\mathrm e}^{-x}+x^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = 2 x \csc \left (x \right )
\] |
✓ |
✓ |
|
\[
{}2 y-x^{3} = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (1-x y\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}2 x +3 y+1+\left (2 y-3 x +5\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime } = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{2} = \left (x^{3}-x y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{3}+y = \left (y^{2} x^{3}-x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (x y-x^{2}\right ) y^{\prime } = y^{2}
\] |
✓ |
✓ |
|
\[
{}\left ({\mathrm e}^{x}-3 x^{2} y^{2}\right ) y^{\prime }+y \,{\mathrm e}^{x} = 2 x y^{3}
\] |
✓ |
✓ |
|
\[
{}x^{2}+y = x y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = x^{2} \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}6 x +4 y+3+\left (3 x +2 y+2\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (x +y\right )-x \sin \left (x +y\right ) = x \sin \left (x +y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{2} {\mathrm e}^{x y}+\cos \left (x \right )+\left ({\mathrm e}^{x y}+y \,{\mathrm e}^{x y} x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } \ln \left (x -y\right ) = 1+\ln \left (x -y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+2 x y = {\mathrm e}^{-x^{2}}
\] |
✓ |
✓ |
|
\[
{}y^{2}-3 x y-2 x^{2} = \left (x^{2}-x y\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x y+\left (x^{2}+1\right ) y^{\prime } = 4 x^{3}
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \sin \left (y\right )-y \sin \left (x y\right )+\left ({\mathrm e}^{x} \cos \left (y\right )-x \sin \left (x y\right )\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y-x^{2}+x \,{\mathrm e}^{y}\right ) y^{\prime } = 2 x y-{\mathrm e}^{y}-x
\] |
✓ |
✓ |
|
\[
{}{\mathrm e}^{x} \left (1+x \right ) = \left (x \,{\mathrm e}^{x}-y \,{\mathrm e}^{y}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}2 x y+x^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x +y+\left (x -y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\ln \left (x \right ) y^{\prime }+\frac {x +y}{x} = 0
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right )-x \sin \left (y\right ) y^{\prime } = \sec \left (x \right )^{2}
\] |
✗ |
✓ |
|
\[
{}y \sin \left (\frac {x}{y}\right )+x \cos \left (\frac {x}{y}\right )-1+\left (x \sin \left (\frac {x}{y}\right )-\frac {x^{2} \cos \left (\frac {x}{y}\right )}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x}{x^{2}+y^{2}}+\frac {y}{x^{2}}+\left (\frac {y}{x^{2}+y^{2}}-\frac {1}{x}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} \left (1+y^{2}\right ) y^{\prime }+y^{2} \left (x^{2}+1\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x \left (x -1\right ) y^{\prime } = \cot \left (y\right )
\] |
✓ |
✓ |
|
\[
{}r y^{\prime } = \frac {\left (a^{2}-r^{2}\right ) \tan \left (y\right )}{a^{2}+r^{2}}
\] |
✓ |
✓ |
|
\[
{}\sqrt {x^{2}+1}\, y^{\prime }+\sqrt {1+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {x \left (1+y^{2}\right )}{y \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } y^{2} = 2+3 y^{6}
\] |
✓ |
✓ |
|